Asuhan Keperawatan Pada Klien Dengan Gangguan Gagal Ginjal Kronik RSUD Kota Bekasi - Risky Ratna Dila; Yuanita Panma (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2019)
Chronic Kidney Failure (CRF) is a progressive and irreversible renal function disorder in which the body fails to maintain metabolism, fluid and electrolyte balance, causing uremia. Hemodialysis is an attempt or an act of cleansing the blood of toxic substances that cannot be excreted by the kidneys from the body. The impact of chronic kidney failure if not treated immediately is hypertension, anemia, pulmonary edema, cardiac tamponade, proteinuria, hematuria, decrease in white blood cells, bleeding disorders, fetor uremic, renal osteodystrophy, psychotic symptoms of convulsions and coma, bruising, excoriation, irregular menstruation . The purpose of writing is expected that students can gain real experience in providing nursing care to clients with chronic kidney failure on HD. The research method is descriptive method and library study. The results of this scientific paper are students gain real experience about providing nursing care to clients with chronic kidney failure on HD. Nursing problems in the form of ineffective airway cleaning, ineffective breathing patterns, risk of damage to gas exchange, high risk of decreased cardiac output, excess fluid volume, risk of nutritional disorders less than body requirements, risk of infection.